#TITLE_ALTERNATIVE# - PRAMESWARIE TARI N. (NIM: 12008009); Tim Pembimbing: Dr. Eng. Suryantini; Ir. Niniek Rina Herdianit
This research contains case study of thermal spring in non volcanic geothermal system in Sulawesi Island. Method used in this research is geochemical technique and considerable study about geological information around thermal spring. This research is provided to understand thermal spring characteristic and its relationship with geological condition, also to recommend exploration concept for development of non volcanic geothermal system, specifically in Sulawesi Island. Data used in this research is analysis of water geochemistry from 42 thermal spring sampels in 16 different geothermal area. Statistic analysis indicate that geology condition is dominant in controlling geochemistry character of thermal spring. The next step is Geochemistry analysis by cluster includes estimation of origin fluid, estimation of reservoir temperature, estimation of water type, observation of pH distribution and physical properties of thermal springs. Thermal spring in study area consist of chloride, chloride-bicarbonate, and bicarbonate with Na-K dominated cation water. Calculated reservoir temperature 110°-200°C. Most of springs water have pH between 6,5-8,6. Factor that controls thermal spring composition is mixing, dilution, water-rock interaction along fault zone and seawater influence. Up flow zone is characterized by the occurrence of chloride water composition with full/partial equilibrium, deposition of silica sinter and high temperature and discharge flow rate. This zone is generally found along/within fault zone. Distal from upflow zone, the water changes into chloride-bicarbonate and bicarbonate water with partial equilibrium. Temperature and discharge are vary but generally high, and often sinter deposit is found. Whereas outflow zone has chloride-bicarbonate or bicarbonate water with immature condition, low temperature and discharge. Thermal spring which influenced by seawater has chloride water with chloride content up to 3000 mg/kg. Thermal spring which come out from limestone has bicarbonate water and probably has bicarbonate element enrichment up to 2000 mg/kg. Exploration concept in determining upflow zone that can be useful as drilling target is searching for area with chloride water in full equilibrium condition, has geothermometer temperature >150°C, high flow rate (more than 1 liter/second), hot thermal spring >70°C, and may be occurrence of silica sinter.